HOUT-25. PROGNOSTIC FACTORS FOR PROLONGED LENGTH OF STAY AND READMISSION FOLLOWING CRANIOTOMY FOR PRIMARY BRAIN TUMORS. (11th November 2019) - Tran, Nam; Amer, Aboubakr; Alhazaimeh, Mohammah; Tran, Quan; Schroering, Ashleigh; Agoris, Corin; Clark, Anthony; Imam, Muhammad; Rao, Gautam; Weisman, Sydney; Dutta, Mudit; Dhanashekar, Anu; et al.
Abstract: BACKGROUND: Escalating costs of healthcare has brought on a paradigm shift that links reimbursement to quality care. Important quality metric measures include hospital length of stay, 30-day readmission and re-operation rates. Identifying modifiable factors can provide information essential for reducing medical costs and improving the quality of medical care patients receive. METHODS: The authors performed a retrospective chart review of all patients who underwent craniotomies for resection of primary brain tumors at the Moffitt Cancer Center from 2004–2014. Patient demographics (age, gender), clinical characteristics (comorbidities, steroid dose, seizure status, neurologic deficit, KPS), tumor characteristics (tumor type, location), surgical factors (primary or redo, length of surgery, blood loss), 30-day complications (infection, DVT/PE, seizure), 30-day readmission, and length of stay were assessed. Multivariate analysis was performed to determine risk factors associated with prolonged length of stay and 30-day readmission. RESULTS: 806 consecutive patients underwent craniotomies for primary brain tumors. High BMI (p< 0.001), CAD (p< 0.001), hyperglycemia (p< 0.04), peri-operative seizures (p< 0.03), low Karnofsky Performance Status score (p< 0.001), prolonged operative times (p< 0.001), and surgical blood loss (p< 0.001) contributed to prolonged length of hospital stay; whereas, preoperative hyperglycemia and perioperative seizures were associated with 30-day readmission. CONCLUSIONS: This study identifies modifiable risk factors that contribute to poorer outcome following craniotomies for primary brain tumors and lays the groundwork for risk stratifying patients undergoing surgery.